Some Innovative Qualitative Data Collecting Techniques - Florentina Scarneci-Domnisoru (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
The article is a plea for more creativity in research. It presents a few methodological innovation procedures accessible to researchers, focusing on new qualitative data collecting techniques. Innovative techniques for observing, interviewing and collecting documents are briefly described. Among others, collaborative and participatory techniques, elicitation techniques, digital and online techniques, visual techniques, etc. are presented. Mention is made, for example, of dyadic interviews, unstructured group interviews, photovoice or analogising.